VALENCY POSSIBILITIES LEXEMES “GRANDCHILD” AND “GREAT-GRANDCHILD” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article is devoted to learn lexical units of kindship, especially “grandson” and “great-grandson”. Also, comparative analysis of valency possibilities are reflected, particular points to consider about meaning of “grandson” and “great-grandson”. as a lexeme in discourse matters are listed in this paper.